CORTICOSTEROIDS- ITS ROLE IN ORAL MUCOSAL LESIONS. - DR.T.SARAVANAN,; DR.M.SUBHA,; DR.P.PREM ANAND,; DR.A.VENKATESH, (International Journal of Pharma and Bio Sciences, 2014)
Glucocorticosteroids have a multitude of effects on many of the stages in inflammatory and immune processes. Corticosteroids are important and widely used therapies in the treatment of a large number of inflammatory and immunologically mediated diseases. However, glucocorticosteroids have proven to be the archetypal ‘double-edged sword of medicine’. The risks associated with corticosteroids parallel the benefits of their therapeutic power. The price for the benefits of corticosteroid therapy may be dear indeed; the side effects are well known. In the content discussed here-long term use of moderate doses to achieve anti-immunologic and anti-inflammatory effects – the special danger is the insidious onset of infection culminating in overwhelming sepsis. Their potential to cause multiple adverse side effects presents the practitioner difficult decision on the management of patients with potentially steroid responsive disorders. The possible beneficial effects of systemic corticosteroids must be weighed against risk factors including their probability of occurrence and their degree of harm. Though the adverse effects of corticosteroids increases with the duration of drug usage based on the risk versus benefits it is used.